Municipal Waste Management in Kushtia District: A Comparative Case Study of Two Municipalities - Md. Ruhul Amin (PT. Altaf Publishing Corp, 2026)
Municipal waste management is a serious problem in developing countries due to rapid urban growth and increasing population. This study compares waste management practices in two municipalities in the Kushtia District of Bangladesh: Kushtia Municipality and Kumarkhali Municipality. The aim is to evaluate the effectiveness and sustainability of their waste management systems. Data were collected through field observations, interviews with municipal officials, and secondary data analysis. The results show clear differences between the two municipalities. Kushtia Municipality has better financial resources and infrastructure, leading to more efficient waste collection, separation, and disposal. In contrast, Kumarkhali Municipality faces major challenges such as limited resources, poor facilities, and low public awareness. These differences are mainly caused by unequal resource distribution, weak community participation, and gaps in policy implementation. The study emphasizes the need for an integrated waste management approach that involves local communities and strengthens institutional capacity. Key recommendations include improving waste separation at the source, using appropriate waste treatment technologies, increasing public awareness, and strengthening monitoring systems. This research provides useful insights for improving municipal waste management and supports efforts to enhance environmental sustainability and public health in urban areas of Bangladesh.